PENGEMBANGAN MEDIA PEMBELAJARAN AUGMENTED REALITY (AR) MENGGUNAKAN ASSEMBLR EDU PADA MATA PELAJARAN IPAS KELAS VI SEKOLAH DASAR - Nurcahaya Pohan, Cici; Media, Afriza; Fitria, Yanti; Fitri, Ummiatul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the suboptimal use of technology in IPAS learning media, which has an impact on student learning. This development created valid, practical, and effective Augmented Reality(AR) learning media based on Assemblr Edu for the IPAS subject in sixth-grade elementary school. This development employed an R&D approach using the ADDIE model. Media validation was obtained through evaluations by subject matter, language, and media experts. The practicality ofthe media was assessed using questionnaires for educators and students. Meanwhile, the effectiveness of the media was determined by comparing pre- and post-tests of students at SDN 35 Parak Karakah and SDN 08 Parak Gadang as pilot schools, as well as SDN 18 Kampung Durian as the research school. The learning media was deemed suitable based on research results that yielded 94.2% content validity, 87.5% media validity, and 95.5% language validity. This media proved to be highly practical for use. Based on teacher feedback of 100% and student feedback of 91.9% at SDN 35 Parak Karakah, SDN 08 Parak Gadang received a teacher response rate of 100% and a student response rate of 90.6%. SDN 18 Kampung Durian also received a practicality score of 95.8% from teachers and 88.9% from students. The effectiveness test yielded an N-Gain score of 0.72 at SDN 35 Parak Karakah, 0.74 at SDN 08 Parak Gadang, and 0.76 at SDN 18 Kampung Durian, with each score falling into the “effective” category. Thus, this AR medium is suitable for implementation in sixth-grade elementary school science education.